Comparison of efficacy of buccal versus vaginal misoprostol in first trimester induced abortion - Khan, Nida; Kant, Anita M.; Thukral, Pooja C.; Saquib, Mohammad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: To compare the effectiveness, side effects, and patient satisfaction of buccal versus vaginal misoprostol administration in first trimester abortions. Methods: Women opting for first trimester abortion received oral Mifepristone followed 48 hours latermisoprostol. Group A received Misoprostol via buccal route whereas group B received Misoprostol vaginally. A comparative analysis using SPSS was done. Results: Giving 800µg Misoprostol by either buccal or vaginal route after oral Mifepristone have comparable efficacy in terms of complete abortion rate (96% in buccal group versus 98% in vaginal group; p value = 0.495), failure rate being statistically similar (4% versus 2%). Drug abortion interval was comparable in the two groups. (11.16 hour in buccal group and 12.32 hours in vaginal group). Few side effects like nausea and vomiting, shivering, diarrohea was significantly higher with vaginal Misoprostol while abdominal cramps, altered taste were found more with the buccal group. Conclusions: Buccal Misoprostol is comfortable and easier to administer when compared to other routes and it has potential to be developed as a self-administered regimen. Buccal Misoprostol is as efficacious as vaginal Misoprostol with significantly lesser side effects up to 7 weeks of period of gestation.